Insights into self-reported food allergies in Romanian schoolchildren - Pop, Claudia Felicia; Rajka, Daniela; Bocsan, Ioana Corina; Coblisan, Petronela Alina; Ichim, Gabriela Edita; Lazar, Anna; Chereches-Panta, Paraschiva (Frontiers in Allergy, 2025)
The prevalence of food allergy (FA) varies worldwide with an increasing rate in the last decades. Data of self-reported FA have been recorded by most European countries, the US, Canada and Australia, but not Romania. The aim of this study is to analyze the prevalence and severity of FA and to assess the extent of information the medical and teaching staff in schools have on students’ medical history.MethodsA cross-sectional survey was performed in schoolchildren from Cluj-Napoca, Romania, using an online questionnaire delivered to their parents.Results and conclusionsSeven hundred and eight individuals completed the entire questionnaire. The prevalence of self-reported FA was 8.9%, 28.6% presented food-induced angioedema and 38.1% required ER presentation. Cow milk (36.5%), egg (9.5%), strawberry (20.6%) and nuts (2.7%)were the most frequent culprit foods. The lack of an appropriate and accurate communication with the medical and teaching staff in the school suggest the requirement for further measures for parents and children educations regarding food allergy detection and management.